2017
DOI: 10.1158/0008-5472.can-16-3167
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Status in CD8+ T Cells Associates with Survival and Anti-PD-1 Therapeutic Outcomes in Head and Neck Cancer

Abstract: Improved understanding of expression of immune checkpoint receptors (ICR) on tumor-infiltrating lymphocytes (TIL) may facilitate more effective immunotherapy in head and neck cancer (HNC) patients. A higher frequency of PD-1+ TIL has been reported in human papillomavirus (HPV)+ HNC patients, despite the role of PD-1 in T cell exhaustion. This discordance led us to hypothesize that the extent of PD-1 expression more accurately defines T cell function and prognostic impact, since PD-1high T cells may be more exh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
148
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(160 citation statements)
references
References 49 publications
10
148
0
2
Order By: Relevance
“…PD‐1 inhibitors can activate partially exhausted cytotoxic T cells and shrink the tumors, but not deeply exhausted T cells . High PD‐1‐expressing CD8 + cells secret less cytotoxic cytokines in vitro, but nivolumab does not subsequently restore the release of cytokines . Although a subset of effector T cells differentiated into effector memory T cells for durable effects of PD‐1 inhibitors, the deeply exhausted T cells were not able to differentiate into effector memory T cells .…”
Section: Discussionmentioning
confidence: 99%
“…PD‐1 inhibitors can activate partially exhausted cytotoxic T cells and shrink the tumors, but not deeply exhausted T cells . High PD‐1‐expressing CD8 + cells secret less cytotoxic cytokines in vitro, but nivolumab does not subsequently restore the release of cytokines . Although a subset of effector T cells differentiated into effector memory T cells for durable effects of PD‐1 inhibitors, the deeply exhausted T cells were not able to differentiate into effector memory T cells .…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent exploratory study reported an 86% response rate to nivolumab in selected lung cancer patients with tumor cells overexpressing PD‐L1 + and low levels of PD‐1 + tumor‐infiltrating lymphocytes . In a mouse cancer model, the antitumor activity of an anti‐PD‐1 antibody was associated with an increase in intratumoral CD8 + cells weakly positive for PD‐1 . Several in vitro studies using flow cytometry have shown that CD8 + cells that highly express PD‐1 release less cytokines and display less cytotoxic activity than cells that weakly express PD‐1 .…”
Section: Discussionmentioning
confidence: 99%
“…10 In a mouse cancer model, the antitumor activity of an anti-PD-1 antibody was associated with an increase in intratumoral CD8 + cells weakly positive for PD-1. 11 Several in vitro studies using flow cytometry have shown that CD8 + cells that highly express PD-1 release less cytokines and display less cytotoxic activity than cells that weakly express PD-1. 11,12 Nivolumab restores the release of cytokines in CD8 + cells that are weakly positive for PD-1, but not in cells that are highly positive for PD-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall survival (OS) of TNBC with rich TILs compared to TNBC with low TILs following adjuvant anthracycline was 89% and 68%, respectively [25]. Some studies did not demonstrate a positive correlation between the presence of TILs and favorable prognoses [26][27][28]. One explanation for this contradiction could be a temporal evolution of TILs, initially involved in rigorous tumor attack and later in the process expire and fatigue.…”
Section: Literature Reviewmentioning
confidence: 99%